Crescimento, produção e qualidade de melão e melancia cultivadas sob extrato de alga Ascophyllum nodosum (L.) - Mendonça Júnior, Antonio Francisco de (Universidade Federal Rural do Semi-Árido, 2015)
The objective was to evaluate the application of commercial compost Acadian®, based seaweed Ascophyllum nodosum (L.) in the productive development and fruit quality of melon and watermelon. The study was divided into two stages and three experiments were carried out similarly for each culture. Experiment I: melon growth under different doses of Acadian® and seed treatment; Experiment II: Melon Growth Acadian® under different application ranges and seed treatments; Experiment III: Production and quality of melon under use of Acadian®. The respective experiments I, II and III were similarly developed for watermelon crop. In the experiments I and II used a completely randomized design in factorial schemes 2x6 and 2x4 respectively, with five repetitions each. The experiment III, in turn, used a randomized block design with 6 treatments and 4 repetitions. In the first trial treatments consisted of the combination of two seed treatments [soaking in drinking water and Acadian®], applying six different doses (0, 1, 2, 3, 4 and 5 mL L-1). In the second trial treatments consisted of the combination of two seed treatments [soaking in drinking water and Acadian®] in four application periods (0, 7, 10 and 14 days), in a dose of 3 mL L-1. In the experiment III treatments consisted of applying a dose of 3 mL L-1, administered in whole or in divided doses (T1: Producer Standard, T2: 2 16 30 (d.a.t.)3; (1 1 1 mL L-1); T3: 2 30 (d.a.t.); (1,5 1,5 mL L-1); T4: 16 30 44 (d.a.t.); (1 1 1 mL L-1); T5: 16 30 (d.a.t.); (1,5 1,5 mL L-1) e T6: 2 (d.a.t.); (3 mL L-1)). Applications via fertigation, 100 mL of the solution prepared by the amount used for each experimental unit. Doses of 3 and 4 mL L-1 product, provided greater increase in the observed variables for both melon and watermelon for both, in turn, had the equivalence of average values of the variables. The watermelon and melon plants referred to applications in intervals of 10 and 14 days showed superior to those that received weekly applications, regardless of seed treatment. Since the product economy, and therefore a reduction in operating costs of production, it allows suggest the use of the lowest dose of product in the longer period, 3 mL L-1 every 14 days for both cultures. The application of Acadian® promoted significant differences in physicochemical parameters evaluated for the two cultures, being observed a distinct behavior among different fractioning the dose. Soluble solids and titratable acidity were within the minimum and maximum limit for commercialization of melon and watermelon
Growth, yield and quality of melon and watermelon plants grown under Ascophyllum nodosum (L.) seaweed extract
Keywords: Melon; Watermelon; Ascophyllum nodosum (L.); Melão; Melancia; Ascophyllum nodosum (L.); CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA